Pengaruh Layanan Konseling Kelompok Teknik Self-Management dalam Mereduksi Perilaku School Refusal Siswa SMAN 15 Pekanbaru - Fathiyah Azizah; Elni Yakub; Kiki Mariah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
School refusal behavior is characterized by a student’s reluctance or lack of motivation to attend school due to emotional difficulties and discomfort experienced within the school environment. This behavior requires timely intervention to prevent adverse academic, social, and personal outcomes. This study examined the effect of group counseling employing self-management techniques on reducing school refusal behavior among students at SMAN 15 Pekanbaru. A quantitative quasi-experimental one-group pretest–posttest design was used. Using purposive sampling, eight eleventh-grade students who scored in the moderate to high range on a school-refusal screening questionnaire were selected. Pretest and posttest scores were compared using the Wilcoxon matched-pairs test, which indicated a statistically significant difference (p = 0.012). Intervention effectiveness was evaluated by mean N-Gain (0.52), indicating a moderate effect. The findings suggest that group counseling with self-management techniques can reduce school refusal behavior in the sampled population. Limitations include the small sample size and absence of a control group, which restrict generalizability. Further research with larger, controlled samples and investigation of precipitating factors and available support systems is recommended.